Komposisi Spesies Penggerek Batang Padi dan Parasitoid Telurnya pada Ketinggian Tempat yang Berbeda - I NYOMAN WIJAYA; WAYAN ADIARTAYASA; KETUT AYU YULIADHI (Fakultas Pertanian Universitas Udayana, 2021)
Composition of Rice Stem Borer Species and Their Egg Parasitoids at Different Altitudes. Rice stem borer is one of the main pest of rice plants that always percolating and attack plants in the field. The pests can result in damage to plants and lost of the grain from season to season. The aim of this research is to know composition and dominance rice stem borer species and role of their eggs parasitoid at an altitude of different places. Research is done by survey based on the height of different altitude in rice plants two weeks after cropping up until eleven weeks after planting. Research conducted from April until August 2019 in rice field that belonging to farmers at Subak Cemagi Let, Cemagi Village and Subak Teba, Mengwi village, Badung regency, Bali province. Subak Cemagi Let are at an altitude of 15 meters above sea level whereas Subak Teba are at an altitude of 300 meters above sea level. Identification of Rice stem borer larvae and their eggs parasitoid done in Pest Laboratory, Agriculture Faculty of Udayana University. Found three species rice stem borer in the height 15 mdpl namely Scirpophaga incertulas; Sesamia inferens dan Chilo suppressalis, whereas in the height 300 mdpl found four species namely Scirpophaga incertulas, Sesamia inferens, Chilo suppressalis, dan Chilo polychrysus. S. incertulas was the most dominant at the two different altitude. Three species of eggs parasitoid that have role to suppress the development of rice stem borer at the different altitude namely Tetrastichus schoenobii, Telenomus rowani dan Trichogramma japonicum. T. schoenobii was the most dominant to suppress rice stem borer populations.